1990
DOI: 10.1016/0031-9384(90)90357-a
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamine and corticosterone levels during active and passive shock-prod avoidance behavior in rats: Effects of chlordiazepoxide

Abstract: Plasma noradrenaline (NA), adrenaline (A) and corticosterone (CS) concentrations were determined in rats before, during and after 15-min exposure to a constantly electrified (2 mA) or nonelectrified prod which was mounted on the wall of the home cage either with or without bedding material on the floor. Concomitantly, exploration of the prod, freezing and prod-burying behavior were recorded. Both in the presence and absence of bedding material, rats explored the nonelectrified prod and showed a small increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 31 publications
(51 reference statements)
4
59
1
1
Order By: Relevance
“…The test was performed in each individual's home cage in order to avoid disturbance of the neuroendocrine and cardiovascular system by intercage transfer (10,22). A removable teflon probe (6.5 cm long, 1 cm in diameter) was inserted 2 cm above the bedding material (wood shavings) through a small hole in the center of the front wall of the Plexiglas cage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test was performed in each individual's home cage in order to avoid disturbance of the neuroendocrine and cardiovascular system by intercage transfer (10,22). A removable teflon probe (6.5 cm long, 1 cm in diameter) was inserted 2 cm above the bedding material (wood shavings) through a small hole in the center of the front wall of the Plexiglas cage.…”
Section: Methodsmentioning
confidence: 99%
“…They were then centrifuged at 4°C for 10 rain at 5000 rpm, and 100 ul of the supernatant were stored at -20°C for CORT and at 80°C for the catecholamine (CA) measurements. Plasma CORT was measured by means of reversed phase high performance liquid chromatography (HPLC), as described earlier (10). Determination of plasma CA concentrations was performed by HPLC in combination with electrochemical detection (23,38).…”
Section: Blood Sarnpling and Cardiovascular Monitoringmentioning
confidence: 99%
“…Rodent burying behavior has long been described as a defensive coping strategy in natural habitats (Calhoun 1962;MacClintock 1970;Owings and Coss 1977). Furthermore, in the context of defensive avoidance, this proactive form of stress management provides an index of anxiety when directed at an electrified probe (Bondi et al 2007;De Boer et al 1990;Korte et al 1992;Treit et al 1981), and is enhanced and attenuated by anxiogenic and anxiolytic drugs, respectively (De Boer and Koolhaas 2003;Diamant et al 1992). To the best of our knowledge, the present studies are the first to specifically characterize and quantify the burying response to i.c.v.…”
Section: Characterization Of Crf-evoked Behaviorsmentioning
confidence: 99%
“…In this test, rats shocked from a stationary, electrified probe push bedding material from the floor of the experimental chamber toward the shock-probe (ie they bury the probe), avoid further contacts with the probe, and exhibit freezing behavior (Treit et al, 1994(Treit et al, , 1981Frye and Seliga, 2003;Pinel and Treit, 1978). In rats it has been demonstrated that anxiolytic drugs such as diazepam decrease burying towards the shock-probe (de Boer et al, 1990;Treit et al, 1993;Tsuda et al, 1988), whereas anxiogenic drugs such as yohimbine increase shock-probe burying (Tsuda et al, 1988). During the training session, burying behavior and the total number of contact-induced shocks each rat received were measured.…”
Section: Shock-probe Burying Testmentioning
confidence: 99%